The Life Skills Training for Children with Mental Disability for Successful Participation in Adult Life: A Systematic Review of Literature - Alikhani, Morteza; Zareii Zavaraki, Esmaeil; Norozi, Daryoosh; Sharifi Daramadi, Parviz; Delavar, Ali (International Journal of Psychosocial Rehabilitation, 2020)
There is little research about the life skills training model for children with mental disabilities for successful participation in adult life. We examined the peer-reviewed literature on the life skills training model for children with mental disabilities. For youth to reach their full potential, a number of critical life skills must be learned. Specific learning opportunities are important, as children with mental disabilities may be limited in the life experiences necessary to acquire these skills. This paper stems from the assumption that training life skills can play an important role in enhancing the successful participation in adult life for children with mental disabilities. A systematic search of the literature spanning 2000 to 2019 was conducted; a comprehensive search through multiple known databases identified a dataset of 91 papers, from which 20 papers met the criteria for in-depth analysis. The analysis revealed that children with mental disabilities often reported a positive impact of life skills training for successful transition to adult life.